Investigation of Power Saving and Optimal Placement of Energy Storage Units in Active Distribution Network with reference to Conservation Voltage Reduction and Contingent Load Configuration - Maddina, Suresh Babu; Thirunavukkarasu, R.; Karthik, N. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The uncertain and intermittent nature of renewable Distributed Generation (DG) components have significant effects on the operation of power system networks causing power quality issues which also reduce the system’s stability. The deployment of Battery Energy Storage Systems (BESS) being the best solution to sustain system stability and power loss minimization. However, the optimal locations and sizes affect the losses of the distribution system and the stochastic loads greatly affect the dynamic stability of the system. The main objective is to determine the bus stops with minimal loss and adequate potential. With the help of optimization techniques like the Genetic Algorithm (GA) and Ant Colony Optimization Algorithms (ACOA), this study aims to find the most efficient placement and size for a BESS, taking into account the power loss reduction afforded by the conservation voltage reduction (CVR) and contingent load (CL) design. The purpose of this work is to find the minimum power loss for the system that still satisfies the equality and inequality requirements. The CVR reduces power consumption relative to load voltage sensitivity via voltage minimization, which in turn improves power balance at the dynamic power scale and, ultimately, grid stability. In order to achieve the best possible decrease in power dissipations and to increase the dynamic stability under unpredictable loads, this research analyzes the optimum capacity and allocation of the DGs in a 33-bus test system. The suggested method is tested against other output and compared to a simulation generated using m-file Matlab code.